3‐aminopyrazolopyrazine derivatives as spleen tyrosine kinase inhibitors. (27th August 2016) - Shen, Jiayi; Li, Xiaokai; Zhang, Zhang; Luo, Jingfeng; Long, Huoyou; Tu, Zhengchao; Zhou, Xiaoping; Ding, Ke; Lu, Xiaoyun
Abstract : A series of pyrazolopyrazine‐3‐amine and pyrazolopyrimidine‐3‐amine derivatives were designed and synthesized as new spleen tyrosine kinase inhibitors. The efforts yielded compound6h with promising spleen tyrosine kinase inhibition in both enzymatic and B‐lymphoma cells proliferation assays. Abstract : Spleen tyrosine kinase is a new promising target for drug discovery to treat human cancer and inflammatory disorders. A series of pyrazolopyrazine‐3‐amine and pyrazolopyrimidine‐3‐amine derivatives was designed and synthesized as new spleen tyrosine kinase inhibitors. The efforts yielded compound6h with promising spleen tyrosine kinase inhibition in both enzymatic and B‐lymphoma cell proliferation assays. Additionally, compound6h dose dependently inhibited the activation of spleen tyrosine kinase signal in human B‐cell lymphoma cells. Compound6h might serve as a lead for further development of new spleen tyrosine kinase inhibitors.